Optimization of hydrogen vehicle refuelling requirements. (11th May 2017) - Bourgeois, T.; Brachmann, T.; Barth, F.; Ammouri, F.; Baraldi, D.; Melideo, D.; Acosta-Iborra, B.; Zaepffel, D.; Saury, D.; Lemonnier, D.
Abstract: The requirements regarding the refuelling process in order to prevent over-heating and over-filling significantly influence hydrogen fuelling station design and have a strong impact on potential fuelling performance. Consequently, refuelling station costs, reliability, and performance can be substantially improved by working on the way these requirements are formulated, in order to achieve shorter fuelling duration with a simpler process and less cooling. Two potential optimization opportunities were extensively investigated in the course of the EU funded HyTransfer project: (i) Application of the temperature limits to the tank material rather than to the gas inside the tank, (ii) Specification of the average delivery temperature rather than of the delivery temperature profile. Multiple research activities were carried out to this end. New models of various types were developed for predicting both the gas and material temperatures inside a vessel during filling and defueling. An experimental programme involving 82 filling and emptying tests of instrumented Type 4 and Type 3 vessels was performed for validating these models. New methods were developed and applied for determining the value of the gas-to-wall heat transfer coefficient from the temperature measurements. The balance of heat transferred from the gas to the liner and to the bosses in a type 4 vessel was reconstructed. CFD simulations were performed for analysing temperature disparities, and the thermal stratification observed in certain filling conditions reproduced. Criteria on gas injection conditions were identified for ensuring gas temperature homogeneity, a key assumption made by fuelling protocols. The temperature variations in the wall material were studied for future investigation of less conservative definitions of the maximum acceptable temperature in Hot Case situations. The effect of changing the delivery temperature profiles without changing the average delivery temperature was also analysed. Highlights: Models are developed to estimate gas and wall temperatures during the filling of H2 tanks. An experimental program has been built to validate these models. Criteria for the appearance of temperature stratification during fillings are proposed. The effect of the inlet temperature profile on the final gas temperature is evaluated.